Unlocking a cryptic pocket: a new approach to safer pain relief - Majumdar, Susruta; Rangari, Vipin Ashok (Henry Stewart Talks, 2026)
CB1 receptor agonists, Cryptic pocket drug design, Molecular dynamics simulations, Peripheral pain therapeutics, Biased GPCR signalling, Tolerance reduction in cannabinoid therapies, Allosteric/sodium binding sites, Translation of analgesic drug candidates (VIP36) to the clinic